Insect pests of grapes in Malaysia - Ibrahim, Rohani (Universiti Putra Malaysia Press, 1993)
All insects attacking various parts ofgrape plants were collected and studied. Six insect pests from 5 families and one mite species were recorded; four species were leaf feeders, two species were stem and vine borers and two species infested fruits. The insect pests were Apogonia cribricolla Burmeister, Hypomeces squamosus Fabricius, Nipaecoccus viridis (Newstead), Protaetia acuminata Fabricius, Vespa tropica Linneaus, and Xylosandrus compactus (Eichhoff). Scolytid borer Xylosandrus compactus was the most serious pest as it killed part of the main vines. The mite species was Tetranychidae, Eutetranychus sp. However, grape planting did not face serious insect problems.